Model test study on the rock mass deformation law of a soft rock tunnel under different ground stresses - Zhu, Zhengguo; Fang, Zhichun; Xu, Fei; Han, Zhiming; Guo, Xiaolong; Ma, Chaoyi (Frontiers in Earth Science, 2022)
It is difficult to monitor the deformation of a rock mass in front of a tunnel owing to the large buried depth and complex geological conditions. In this study, by using a self-designed model test box as a carrier and using loess, sand, gypsum, cement, and water as the raw materials, the class V materials similar to the surrounding rock are obtained through an orthogonal test. These are used to study the deformation law of a rock mass in front of a tunnel in different ground stress soft rock. The results show that similar materials for the surrounding rock can meet the needs of the testing concerning the physical and mechanical properties and have economic and environmental protection advantages. The three-dimensional loading of a similar geological body is used to simulate the state of the rock mass. The real-time monitoring of the rock mass stress and deformation is conducted during a simulation of tunnel excavation, and the deformation laws of the rock mass and surrounding rock in front of the tunnel are obtained. In the range of 0.26 times the tunnel diameter in front of the tunnel in the high ground stress soft rock, the deformation of the core rock mass is the largest part of the tunnel deformation. Therefore, to reasonably control the advanced deformation of the tunnel, it is necessary to pre-reinforce the core rock mass within 0.26 times the tunnel diameter in front of the tunnel. At 1 times the diameter in front of the face, a longitudinal load-bearing arch is formed in the rock mass, and this effectively controls the extrusion deformation of the core rock mass to expand forward.